Postoperative Euglycaemic Diabetic Ketoacidosis Associated with Sodium–Glucose Cotransporter-2 Inhibitors (Gliflozins): A Report of Two Cases and Review of the Literature. Issue 2 (March 2018) - Chacko, B.; Whitley, M.; Beckmann, U.; Murray, K.; Rowley, M.
Sodium–glucose cotransporter-2 inhibitor (SGLT2i)-associated euglycaemic diabetic ketoacidosis (euDKA) is a serious and increasingly recognised complication of treatment with this class of oral hypoglycaemic agents and can present a diagnostic challenge, resulting in delayed recognition, inappropriate treatment and potentially life-threatening acidosis. We present two cases of patients developing SGLT2i-associated euDKA in the early postoperative period. We support ceasing SGLT2i for 72 hours preoperatively and would suggest continuing to withhold the medication until oral intake is restored, and recommend a wider awareness of SGLT2i-associated diabetic ketoacidosis (DKA) amongst patients and their healthcare providers with an emphasis on checking ketone levels irrespective of blood glucose levels in the postoperative setting.